MENJADI PENONTON TELEVISI YANG BERDAYA - shinta prastyanti (Jurnal Ilmu Komunikasi Acta Diurna, 2014)
It is a fact that since several decades television has become one one the most favourite medium for the audience. Television’s ability to hypnotise makes the audience do not reluctance to spend their time for hours in front of television. The variety of television programs become the alternative choice for the audience. Today, watching television as if a need for the people. The impacts are not only on the watching aspect, but it is also in content side. Television programming is like the truth and it should be convinced the audience. There is no restriction to watching television, but it will be better if people do not empower by television. The audiences should become empowered television viewers. Empowered in this case, the audience can choose and select an appropriate program which is matching with their need and using the television’s information as a modal to control their environment.